Quality of family planning counseling and associated factors among reproductive age women who are current contraceptive users at Dessie town health facilities east Amhara, 2023 - Nigusie Abebaw; Berihun Haile; Amare Workie; Wondwosen Mebratu; Molla Getie (BMC, 2024)
Abstract Background The role of counseling in Family Planning is to care a woman in navigating the process of choosing a contraceptive method that will allow her to fulfill her family planning goals and exercise her reproductive health rights. The effectiveness and appropriateness of family planning counselling play a crucial role in a client's decision-making process regarding contraception. The decision for a client to use contraception with effectively and properly it should be ultimately achieved the quality of family planning counclling. The aim of this research is to assess quality of family planning counseling and associated factors among reproductive age women at Dessie town health facilities, east Amhara, Ethiopia, and 2023. Methods A facility based cross-sectional study was conducted from December 1, 2022- January 30, 2023. Study subjects were selected by using systematic random sampling method. Data was be collected by exit interview of the women and analyzed by SPSS version 26.  Bivariable and Multi variable logistic regression were executed to identify associated factors with quality of family planning counseling and the P- Value <0.05 on Multi variable analysis was considered as significantly associated with the dependent variable. Result The proportion of women receiving good quality family planning counselling in this study was 36.5%.  Contraceptive source [AOR=2.03, 95%CI (1.09, 3.75)], Contraceptive currently used [AOR=0.43, 95%CI (0.26, 0.73)], separate room for family planning counseling [AOR=3.38, 95%CI (1.09, 3.75)] and availability of all methods [AOR=3.10, 95%CI (1.85, 5.21)]were significantly associated with quality of family planning counselling. Conclusion The proportion of women obtaining good quality FP counseling in this study low. Type of contraceptives currently used, source of contraceptives, separate room for providing family planning counseling and availability of all methods of family planning in the facility are significantly associated with quality of family planning counseling. Therefore, all health profession could be given proper counseling to increase the quality of family planning.